The genetic variation of a mitochondrial and two behaviour‐related genes in invasive African Sacred Ibis (Threskiornis aethiopicus) populations in Taiwan - Ku, Yu‐Chia; Chen, Yu‐Chi; Hung, Chih‐Ming; Ng, Chen Siang (Ibis (London, England), 2023)
The African Sacred Ibis Threskiornis aethiopicus is an invasive bird species in Taiwan and has expanded its distribution range rapidly over the past three decades. There is limited information available on the invasion process of African Sacred Ibises in Taiwan and its genetic consequences. We investigated whether genetic factors reflected the expansion of African Sacred Ibises and determined the extent to which two behaviour‐associated genes may have facilitated invasion. The dopamine receptor gene (DRD4) and the serotonin transporter gene (SERT) have both been found to be associated with novel‐seeking and bold behaviour in birds. We hypothesized that: (1) selection on temperament traits may determine the polymorphisms in these two genes and (2) the likelihood of dispersal of African Sacred Ibis populations can be explained by the intraspecific variation at these two genes. To detect the signals of population expansion and natural selection, we compared intra‐population variation and inter‐population differentiation of DRD4 and SERT with those of a mitochondrial gene (COX1) and an additional intron. We recovered contrasting patterns of nucleotide variation between the mitochondrial and nuclear genes with no single nucleotide polymorphisms detected in COX1 compared with allelic polymorphism in DRD4 and SERT. Populations showed decreasing genetic diversity at DRD4 as their distance to the initial invasive locality increased, consistent with a rapid expansion from one founder population. However, we found little evidence of selection on DRD4 or SERT, suggesting that these behaviour‐related genes are unlikely to have played a significant role in the successful invasion of the African Sacred Ibises in Taiwan. We detected high levels of genetic variation at these two behaviour‐related genes despite the effects of inbreeding in these invasive birds.